Концепція смарт-спеціалізації в контексті розвитку економіки України - Bublyk, Myroslava; Udovychenko, Tetiana; Medvid, Roman (Dr. Viktor Koval, 2019)
Introduction. Over recent years, Ukraine has made considerable efforts in shaping the current state policy for the development of regions, where priority development of the territories is a further reformation of the system, which together will ensure the country's economic growth.   Therefore, it is precisely today that has never before been given special attention to the European innovation concept of the development of regions on the basis of smart specialization. Aim and tasks. The purpose of the article is to study the peculiarities of the smart specialization approach to the development of the policy of regional development of Ukraine, namely: 1) studying the concept of smart specialization, its principles and essence; 2) determining the boundaries specialization as a tool in the development of the region;            3) development of recommendations based on the use of analytical methods to identify potential priority areas of smart specialization. Results. The article analyzes smart-specialization, as an instrument of regional development, allows to integrate the key aspects of vital functions and development and instrumental in an active collaboration and co-operation of different participants of process of development for the sake of creation of general prospect, and also foresees creation of unique resources and possibilities on the basis of unique industrial, of a particular branch structures and proper base of knowledge. The use of smart-specialization, as to the instrument of development of regions, is regulated four simple rules: choice and critical mass; competitor advantage; interconnection and clusters; general management, - that behave to the sphere of researches and innovations which are also used in other spheres, and in particular to social, economic, protective environment and others like that. Conclusions. For Ukraine, implemented models of smart specialization is an urgent task, and on its basis it is possible to unlock the regional potential for structural and technological changes, as well as industrial modernization of innovative principles. This is important in terms of overcoming the destructive tendencies of conservation of the inefficient economic structure of the regions of Ukraine based on the artificial identification of certain industrial regions as priority.